Analisis dan Perancangan Sistem Informasi Manajemen Karyawan di PT. Regista Bunga Wijaya Cabang Surabaya - Teguh Herlambang (Walisongo Journal of Information Technology, 2023)
In the Human Resources Development (HRD) division at PT Regista Bunga Wijaya Surabaya branch, one of the main targets is the fulfillment of personnel. In meeting this target, HRD always opens job vacancies. To manage the number of employees who apply and select employees who are in accordance with the needs and criteria of the client, it takes a long time if you have to look at job applications one by one. In addition, to manage a Temporary Appointment Work Agreement, the employee salary component, and the current employee turn over are still conventionally recorded using Microsoft Excel. So that a system is needed that facilitates, speeds up and facilitates the process of employee accession and human resource management. The system needed is in the form of an Employee Management Information System to meet the needs of PT Regista Bunga Wijaya Surabaya branch, especially for the HRD division. In this study, a method of collecting system needs was used using a combination of techniques in the form of document analysis, brainstorming, and also prototyping. Information System The results of this study in the form of an employee management information system application design which includes employee fulfilment, employee data, and employee turn over at PT Regista Bunga Wijaya Surabaya branch can be used as a reference for PT Regista Bunga Wijaya Surabaya branch to be implemented into a system used as a support for company operations.